Evaluation the Possible Role of Interleukin-6 and Tumor Necrosis Factor- Alpha in Pathogenesis of Obstructive Sleep Apnea in Obese Patients: A Case-Control Study : - Minaeian, Sara; Rahmani Fard, Soheil; Ahsant, Samaneh; Riahi, Taghi; Taheri Tinjani , Reyhaneh; Alimohamadi , Yousef; Kooranifar, Siavash; Shamlou Mahmoudi, Fatemeh; Hosseinipour, Ali (Galen Medical Journal, 2022)
Background: According to a mounting body of evidence, recent observations have highlighted considerable association between obstructive sleep apnea (OSA) syndrome and patients’ obesity and inflammation, however the exact underlying mechanisms remain to be fully understood. In this study, the relationship between OSA and Interleukin-6 and Tumor necrosis factor- alpha was assessed in obese patients and their serum concentrations were compared to non-OSA obese subjects. Materials and Methods: This case-control study was conducted on forty-six obese OSA patients (body mass indices, BMI>30) and 42 obese but otherwise healthy individuals who were admitted to the pulmonary or obesity clinics of the Hazrat-e Rasool General Hospital (Tehran, Iran) between November 2019 and May 2020 were included. The participants completed the NOSAS, EPWORTH and STOPBANG questionnaires. Tumor Necrosis Factor-Alpha (TNF-α) and Interleukin-6 (IL-6) serum concentrations were determined using the enzyme-linked immunosorbent assay (ELISA) method. Results: Compared to the non-OSA group, OSA patients had higher systolic and diastolic blood pressure, pCO2, bicarbonate (HCO3) and hemoglobin and lower high-density lipoprotein (HDL) values. IL-6 and TNF-α serum levels were not significantly different between both groups. Univariate and multivariate linear regression models showed that BMI, systolic blood pressure, pCO2 and HCO3 can positively affect the serum TNF-α and systolic blood pressure and HCO3 can also positively affect the serum IL-6 values in patients with the OSA. Conclusion: This investigation suggests that among the OSA patients, the heightened inflammatory profile may be influenced by the high BMI. Furthermore, the exclusive relationship between different disease biomarkers and inflammatory agents in OSA patients is intriguing and needs further research.